The European Convention on Human Rights and Church-State Relations. Pluralism vs. Pluralism (Stato, Chiese e pluralismo confessionale, 2011)
SUMMARY: INTRODUCTION: Key Provision – An Indirect Regulation - The Court is Not a Constitutional Court - Judicial Restraint - A Vision of Religious Freedom - Institutional Dimension of Religious Freedom - I. MODELS: No Arbitrary State Interference - State Neutrality and Impartiality - II. COUNTER-MODELS: Islam – Sects.